Development of a test method to compare dynamic parameters of sports shoes - De Raeve, E.; Vertommen, H.; Peeraer, L.; Muraru, L. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Shoe properties like anti-pronation [1] damping and flexibility [2] can play an important role in reducing the risk of running injuries. However it is difficult to evaluate different sport shoe types considering above mentioned parameters. This work belongs to a larger project aiming to develop a test protocol for measuring a number of relevant shoe parameters, independent of shoe size, shoe type and runner, but measured in real running conditions. METHODS: 55 healthy persons ran 10 times with 5 different running shoes. Ground reaction force and 3D movement of shoe sole and shank were recorded simultaneously with a force plate (Amti) and a motion tracking system (Codamotion) with a 28 markers protocol. According to the manufacturer shoe 1 is an antipronation shoe, shoe 2 is a neutral but very flexible shoe, shoe 3 has good shock absorption properties, shoe 4 is an antipronation shoe and shoe 5 is a reference shoe. Five shoe parameters were calculated: the angle between calcaneus and Achilles tendon and the angle between heel and ground (antipronation), the steepness of the active peak of the ground reaction force (damping) and the sagital and torsional bending magnitude in the forefoot (flexibility). A paired t-test was done for all parameters between every couple of shoe types. RESULTS: Both antipronation parameters of shoe 1 are significantly different (p<0.001) than all other shoes. 84% of the test persons has a more controlled unroll of the heel when running with shoe 1 that with shoe 5. Shoe 2 is significantly more flexible (p<0.001) than all other shoes. 72% of the test subjects bent the forefoot at least 10% more when running with shoe 2 compared to shoe 5. Shoe 3 has a significant higher damping than all the other shoes (p<0.001). There is no statistically significant difference of antipronation properties between shoe 4 and the reference shoe. DISCUSSION: A method to quantify shoe parameters and to compare different shoes was developed. Shoe manufacturers can obtain truthful feedback about shoe properties. Although according to the manufacturer shoe 4 should be antipronating, there is no difference in the chosen anti-pronation parameters. All other distinct shoe features given by the manufacturers were proven by measurements. To make statistical relevant results in a smaller time frame, we are transferring the measurement protocol to our robotic gait simulator.